Mechanism Sharing Between Genetic and Gestational Hypoxia-Induced Cardiac Anomalies - Moumne, Olivia; Chowdhurry, Rajib; Doll, Cassandra; Pereira, Natalia; Hashimi, Mustafa; Grindrod, Tabor; Dollar, James J.; Riva, Alberto; Kasahara, Hideko (Frontiers in Cardiovascular Medicine, 2018)
Background: Cardiac development is a dynamic process both temporally and spatially. These complex processes are often disturbed and lead to congenital cardiac anomalies that affect approximately 1% of live births. Disease-causing variants in several genetic loci lead to cardiac anomalies, with variants in transcription factor NKX2-5 gene being one of the largest variants known. Gestational hypoxia, such as seen in high-altitude pregnancy, has been known to affect cardiac development, yet the incidence and underlying mechanisms are largely unknown. Methods and Results: Normal wild-type female mice mated with heterozygous Nkx2-5 mutant males were housed under moderate hypoxia (14% O2) or normoxia (20.9% O2) conditions from 10.5 days of gestation. Wild-type mice exposed to hypoxia demonstrate excessive trabeculation, ventricular septal defects, irregular morphology of interventricular septum as well as atrial septal abnormalities, which overlap with those seen in heterozygous Nkx2-5 mutant mice. Genome-wide transcriptome done by RNA-seq of a 2-day hypoxic exposure on wild-type embryos revealed abnormal transcriptomes, in which approximately 60% share those from Nkx2-5 mutants without hypoxia. Gestational hypoxia reduced the expression of Nkx2-5 proteins in more than one-half along with a reduction in phosphorylation, suggesting that abnormal Nkx2-5 function is a common mechanism shared between genetic and gestational hypoxia-induced cardiac anomalies, at least at a specific developing stage. Conclusion: The results of our study provide insights into a common molecular mechanism underlying non-genetic and genetic cardiac anomalies.